COMPARISON OF CONSUMER LIFESTYLE SEGMENTATION MODELS: APPLICATIONS OF AIO, VALS, LOV, AND LOHAS MODELS - Baldangombo, Ugtakhargal; Batsukh, Davaasuren; Yadamsuren, Otgonsuren (Journal of Business and Innovation (Бизнес & Инноваци), 2025)
Lifestyle segmentation models serve as important analytical tools for understanding consumer behavior, preferences, and purchase decision-making processes. These models classify consumers into lifestyle-based segments by analyzing psychological and social factors such as daily activities, interests, values, opinions, and attitudes. As a result, they enable marketers to develop more targeted strategies, optimize product development, strengthen brand positioning, enhance communication, and increase customer loyalty. This study reviews four widely used lifestyle segmentation models: AIO (Activities, Interests, Opinions), VALS (Values and Lifestyles), LOHAS (Lifestyles of Health and Sustainability), and LOV (List of Values). Each model has its own historical background, theoretical foundation, research methodology, and application scope. The aim of this research is to analyze and compare these models from both theoretical and practical perspectives.